The Effect Of Strategic Supply Partnership And Customer Relationship On Business Performance Through Competitive Advantage (Study on Tofu Industry in Kampar Regency) - Paramitha, Anggia; Berampu, Lailan Tawila; Nurfiansyah, Ulfah (Mahesa Research Center, 2026)
This study aims to test and analyze the effect of strategic supplier partnership and customer relationship on business performance through competitive advantage as an intervening variable in the tofu industry in Kampar Regency. The population in this study were all tofu industries in Kampar Regency in 2023, namely 124 businesses. This study used a quantitative approach with the technique of probability sampling, namely by using cluster sampling in as many as 53 tofu industries. The analysis method used is SmartPLS. The results showed that strategic supplier partnership has a positive and significant effect on competitive advantage. Customer relationship has a positive and significant effect on competitive advantage. Strategic supplier partnership has a positive and significant effect on business performance. Customer relationship has a positive and significant effect on competitive advantage. Competitive advantage has a positive and significant effect on business performance. Competitive advantage can mediate the effect between strategic supplier partnerships on business performance. Competitive advantage can mediate the effect of customer relationships on business performance.